2013
DOI: 10.4319/lom.2013.11.316
|View full text |Cite
|
Sign up to set email alerts
|

Estimating modern carbon burial rates in lakes using a single sediment sample

Abstract: The rate of organic carbon (OC) burial in inland waters is an important flux in the global C-cycle. Here we provide methodological improvements that offer a rapid and accurate assessment of modern OC burial rates in lakes from a single surface-sediment sample. Using a 93 lake dataset of reliably dated sediment cores (OC burial of 9 to 318 g m -2 y -1 ), we demonstrate the applicability of this approach in a variety of lake types. We validate our estimated rates of OC burial against (1) measured whole-lake accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The OC flux per area for another LC lake (LD‐1, located in the outer delta, 211 ± 25 gCm −2 year −1 averaged over the core, n = 16, Figure 1) is between the fluxes observed for MD‐2 and UD‐4. All these values are comparable to observations from lakes in the northern USA (9–318 gCm −2 year −1 , Hobbs et al., 2013). Overall, the median carbon flux encountered in lakes around the world is 40 gCm −2 year −1 (not counting reservoirs, see Mendonça et al., 2017) is not really representative of the Mackenzie Delta lakes which show a large range of values.…”
Section: Discussionsupporting
confidence: 89%
“…The OC flux per area for another LC lake (LD‐1, located in the outer delta, 211 ± 25 gCm −2 year −1 averaged over the core, n = 16, Figure 1) is between the fluxes observed for MD‐2 and UD‐4. All these values are comparable to observations from lakes in the northern USA (9–318 gCm −2 year −1 , Hobbs et al., 2013). Overall, the median carbon flux encountered in lakes around the world is 40 gCm −2 year −1 (not counting reservoirs, see Mendonça et al., 2017) is not really representative of the Mackenzie Delta lakes which show a large range of values.…”
Section: Discussionsupporting
confidence: 89%
“…Sediments were freeze‐dried and analyzed for 210 Pb activity by alpha spectroscopy. We used the method described by Hobbs et al () to estimate C burial rates based on a single sample from each lake. Submersed macrophyte biomass and phytoplankton abundance in the 60 lakes were also sampled annually from 2009 to 2011 with the methods described previously.…”
Section: Methodsmentioning
confidence: 99%
“…OC burial rates at core sites were calculated by multiplying bulk sediment accumulation rates by the proportion of OC in dry sediment. We corrected OC burial estimates from individual core locations for sediment focusing [13] by multiplying the sedimentation rate by the ratio of the expected, regional unsupported 210 Pb inventory (33.5 dpm cm -2 ) [25] to the observed unsupported 210 Pb inventory. This correction was adjusted for cores from Lake Lochloosa, where whole-basin analysis of 13 210 Pb-dated cores indicated that the mean unsupported 210 Pb inventory was lower (21.3 dpm cm -2 ) than the putative regional value.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple paleolimnological techniques can be used to estimate OC burial in lakes. They range from the rapid, single-core method, to the intensive, whole-basin approach [13]. Recent OC burial estimates are typically derived from analysis of multiple 210 Pb-dated sediment cores [5] and provide information about OC sequestration during the previous ~100 years, sometimes at sub-decadal temporal resolution.…”
Section: Introductionmentioning
confidence: 99%